Utility of perfusion PET measures to assess neuronal injury in Alzheimer's disease. Issue 1 (27th September 2018) - Joseph‐Mathurin, Nelly; Su, Yi; Blazey, Tyler M.; Jasielec, Mateusz; Vlassenko, Andrei; Friedrichsen, Karl; Gordon, Brian A.; Hornbeck, Russ C.; Cash, Lisa; Ances, Beau M.; Veale, Thomas; Cash, David M.; et al.
Abstract: Introduction: 18 F‐fluorodeoxyglucose (FDG) positron emission tomography (PET) is commonly used to estimate neuronal injury in Alzheimer's disease (AD). Here, we evaluate the utility of dynamic PET measures of perfusion using 11 C‐Pittsburgh compound B (PiB) to estimate neuronal injury in comparison to FDG PET. Methods: FDG, early frames of PiB images, and relative PiB delivery rate constants (PiB‐R1) were obtained from 110 participants from the Dominantly Inherited Alzheimer Network. Voxelwise, regional cross‐sectional, and longitudinal analyses were done to evaluate the correlation between images and estimate the relationship of the imaging biomarkers with estimated time to disease progression based on family history. Results: Metabolism and perfusion images were spatially correlated. Regional PiB‐R1 values and FDG, but not early frames of PiB images, significantly decreased in the mutation carriers with estimated year to onset and with increasing dementia severity. Discussion: Hypometabolism estimated by PiB‐R1 may provide a measure of brain perfusion without increasing radiation exposure.